PsychiatryOnline. Issue 3 (1st October 2020) - Loper, Kimberly A.
Abstract: The American Psychiatric Association (APA) is the world's largest professional organization for the field of psychiatry. PsychiatryOnline is available through the APA's publishing division the American Psychiatric Association Publishing, which is a leading publisher of psychiatry materials. PsychiatryOnline is a web-based application that is regarded as an authoritative clinician-oriented web site and provides access to peer-reviewed journal publications plus access to one of the field's most important resource, the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) .